The Role of GDP in Changing the Influence of Environmental and Politic on SDG - Anum Nuryani; Anggun Anggraini; Andika Prasetya (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2025)
Amidst the current changing global conditions, it is important for a country to achieve the Sustainable Development Goals (SDGs) to face challenges in sustainable development, social inequality, and strengthen economic and environmental resilience. This study aims to analyze the influence of environmental performance and political stability on the SDG scores of ASEAN countries for the 2020-2024 period, moderated by economic growth. Researchers used a quantitative method, processed using multiple linear regression with SPSS. The regression process was conducted twice, before and after using moderating variables. The findings suggest that economic growth can alter the influence of environmental performance and political stability on SDG scores. Political stability has a positive impact on the SDGs after economic growth has moderated. While environmental performance has a negative impact after being moderated by economic growth. Economic growth promotes political stability and sustainable growth. Conversely, with high growth, improvements in environmental performance are indicated to shift priorities from sustainability to exploitation.